Poland in the European Union – Reaching Beyond the Liberal Perspective of Analysis - Więcławski, Jacek (Przegląd Strategiczny, 2016)
The article refers to Polish membership in the European Union and the liberal perspective of its analysis. The paper discusses the shortages of the liberal approach. The article accepts the liberal thesis regarding the opportunities that the accession to the EU opens up for Polish development. It notes the significance of the European mechanisms of regional cooperation. Nevertheless, the paper emphasises that the liberal perspective ignores the inequalities of power in the European Union and misses some serious tendencies, both at the level of the community and in the domestic politics, that impede the state’s development. Thus, the article refers to the limited competitiveness of the Polish economy and the state’s difficulties with the identification of its interests in the dynamic and variable international environment. It warns against the marginalization of Poland as “semi-peripheral” member of the European Union. The main conclusion of the paper is that the case of Polish membership in the EU is too complicated to close it in the liberal frameworks. The liberal perspective needs a realist correction. It is extremely important in the context of the challenges that Poland faces together with the crisis of the European integration.